Ungleiche Geschlechtergleichheit Geschlechterpolitik und Theorien des Humankapitals - Casale, Rita; Forster, Edgar (Jahrbuch Frauen- und Geschlechterforschung in der Erziehungswissenschaft, 2011)
Old and new order of the sexes: on the one hand - as neoconservatism says - men and women are completely equal: Equal opportunities seem to have been achieved. On the other hand, liberal individualism says that the differences between the sexes are of enormous importance. Are these two sides of the same coin? The authors analyse this contradiction from a pedagogical perspective. The "Jahrbuch Frauen- und Geschlechterforschung in der Erziehungswissenschaft" is based on an important scientific and political development. Women's and gender studies in educational science has contributed significantly to the fact that the influence of gender and gender difference can no longer be ignored. The Yearbook is conceived against this background and has two central tasks: First, it aims to continuously document gender studies in educational science and, second, to create an innovative forum for scientific discourse. All articles are reviewed according to the international standard for review journals.